Analysis of The Influence of Trust In Digital Transactions and Website Reputation on Customers Purchase Intention Through Footwear Website - Setianti, Yanti; Budi Sulistiarini, Emma; Sugiharto, Bambang; Elizabeth; Syaifudin, Arif (SEULANGA SYSTEM PUBLISHER, 2024)
This study examines how attitudes regarding online buying and the consequences for purchase intention are influenced by perceived website repute, relative advantage, perceived website image, and trust. Researchers employed a survey method in this study to conduct descriptive research. A questionnaire was used in this survey approach. E-commerce consumers who reside in Jabodetabek make up the study's population. Using judgmental sampling, the researcher employed a non-probability sampling technique. In this study, the single-cross-sectional approach was employed for data collecting. The structural equation model method will be used to analyze the data. Amos is the program that's being used. According to the data processing results, it was discovered that, in the first place, relative profits, trust, and website image are all significantly positively impacted by perceived website reputation. Second, trust, the perception of websites, and attitudes toward online commerce are considerably improved by relative advantage. Third, perceptions of websites have a detrimental effect on attitudes toward internet buying. Fourth, sentiments toward internet purchasing are positively impacted by trust, though not much. Opinions regarding internet purchasing significantly positively influence fifth intentions to purchase. This demonstrates that consumers' intentions to buy through a website positively correlate with their attitude about online buying.